Meropenem/vaborbactam activity against carbapenem-resistant Klebsiella pneumoniae from catheter-related bloodstream infections - Francesca Sivori; Massimo Francalancia; Mauro Truglio; Ilaria Cavallo; Carmelina Pronesti; Giorgia Fabrizio; Ilaria Celesti; Andrea Cazzani; Lorenzo Furzi; Fulvia Pimpinelli; Enea Gino Di Domenico (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCarbapenem-resistant Klebsiella pneumoniae (CRKP) poses a significant threat in oncology settings due to its multidrug resistance and ability to form biofilms on indwelling medical devices.MethodsThis study investigated the in vitro and in vivo activity of meropenem/vaborbactam (MEV) against two CRKP isolates recovered from catheter-related bloodstream infections in patients undergoing orthopedic oncologic surgery.ResultsWhole-genome sequencing identified the isolates as ST101 and ST307, harboring resistance determinants including blaKPC-3 and blaOXA-1, distributed across IncFII and IncFIB plasmid replicons. Both isolates exhibited extensive resistance to β-lactams, aminoglycosides, and fluoroquinolones but remained susceptible to MEV. Phenotypic assays revealed enhanced biofilm formation and metabolic activity compared to the reference strain Kp ATCC 13883 in the absence of hypervirulence-associated genes. MEV demonstrated bactericidal activity against both planktonic and biofilm-associated cells, with minimum bactericidal concentration (MBC90) and minimum biofilm eradication concentration (MBEC90) values of 0.5/8 μg/ml for CRKP ST101, 0.12/8 μg/ml for CRKP ST307, and 0.25/8 μg/ml for the Kp ATCC 13883 strain. In the Galleria mellonella infection model, MEV significantly improved larval survival following the CRKP challenge.DiscussionThese findings demonstrate that MEV exhibits activity against planktonic and biofilm-associated CRKP cells and highlight the need for further investigation in managing catheter-related bloodstream infections caused by multidrug-resistant K. pneumoniae.